2011
DOI: 10.1186/bcr2834
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 can be used for further classification of triple negative breast cancer into two subtypes with different response and prognosis

Abstract: IntroductionTriple negative breast cancer (TNBC) has a poorer survival, despite a higher response rate to neoadjuvant chemotherapy. The purpose of this study was to identify the predictive or prognostic value of Ki-67 among patients with TNBC treated with neoadjuvant chemotherapy, and the role of Ki-67 in further classification of TNBC.MethodsA total of 105 TNBC patients who received neoadjuvant docetaxel/doxorubicin chemotherapy were included in the present study. Pathologic complete response (pCR) rate, rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
151
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(174 citation statements)
references
References 38 publications
18
151
3
2
Order By: Relevance
“…This is in agreement with data in the literature, which show that, in such patients, the tumor is more aggressive, the incidence of distant metastases, particularly in visceral organs such as the lung, is higher, and survival is lower. (5,11,(15)(16)(17)(18) We found that there was a tendency toward a worse prognosis in patients who had been diagnosed with a primary tumor before 50 years of age, perhaps suggesting that diagnosis after the age of 50 is a protective factor. The prognosis for breast cancer is relatively good if it is diagnosed in the early stages.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This is in agreement with data in the literature, which show that, in such patients, the tumor is more aggressive, the incidence of distant metastases, particularly in visceral organs such as the lung, is higher, and survival is lower. (5,11,(15)(16)(17)(18) We found that there was a tendency toward a worse prognosis in patients who had been diagnosed with a primary tumor before 50 years of age, perhaps suggesting that diagnosis after the age of 50 is a protective factor. The prognosis for breast cancer is relatively good if it is diagnosed in the early stages.…”
Section: Discussionmentioning
confidence: 71%
“…(18,24,25) The worst breast cancer survival rates are in developing countries. (26,27) Survival in malignant pleural effusion has also been widely studied.…”
Section: Resultsmentioning
confidence: 99%
“…There is no report about the relationship between these two factors and TNBC imaging features. Keam et al (2011) reported that a high Ki-67 expression was significantly associated with poor RFS and OS in TNBC, regardless of the pathologic complete response (PCR). This finding is similar for p53 in TNBC (Chae et al, 2009), which when positive or overexpressed, resulted in non-ideal or poor RFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival (OS)rate is lower in the p53 (+) group than in the p53 (-) group (Chae et al, 2009). A high Ki-67 expression is associated with poor relapse-free survival (RFS) and OS in TNBC (Keam et al, 2011). TNBC accounts for 11%-20% of all sub-types of breast cancer (Itoh et al, 2006).…”
Section: Associations Between Mammography and Ultrasound Imaging Featmentioning
confidence: 99%
See 1 more Smart Citation